Practices on oral rehydration solution among the caregivers of inpatient children in two tertiary paediatric units, Kandy district - Thusthika, A.; Kudagammana, S.T. (University of Jaffna, 2022)
Oral rehydration solution plays a major role in the management of diarrhoea at the home setting. Though the effectiveness of oral rehydration solution is proven, the benefit depends on proper usage. This in turn depends on the practices of caregivers. The study aimed to assess the prevalence and the practices of oral rehydration solution usage among caregivers of inpatient children. This is a descriptive cross-sectional study conducted among 316 caregivers of children in the paediatric medical wards of Sirimavo Bandaranayke Specialized Children Hospital and professorial paediatric ward of Teaching Hospital Peradeniya, Sri Lanka. A pre tested self-administered questionnaire in preferred language was used to collect data. Data were anysed using IBM SPSS version 25.0. Chi-square test and frequency tables were used to describe the findings. The prevalence of oral rehydration solution usage during the past six months was 62.04%. Out of all, 29.4% had poor while 70.6 % had good practices in oral rehydration solution usage. Among all caregivers, 51.3% had never used oral rehydration solution without getting medical prescriptions. The majority had always used boiled cooled water to prepare oral rehydration solution (68%), stored it at room temperature (53.5%), discarded it after 24 hours of its preparation (63.9%), and washed hands before preparing the oral rehydration solution (67.4%). Nearly 30% had always initiated Oral rehydration solution administration after the passage of loose stools >2 times and had oral rehydration solution packets at home although their children did not have diarrhoea. 81.6% of the caregivers had never prepared home-made oral rehydration solution when an oral rehydration solution sachet was not available. The practices of the caregivers were associated with relationship to the child, educational qualifications, and ethnicity (p< 0.05). Although more than 70% had good practices in oral rehydration solution usage, there is a misconception that medical prescriptions are needed to take oral rehydration solution. Education about homemade oral rehydration solution, and initiation of oral rehydration solution is recommended. Having an oral rehydration solution sachet at home should be encouraged among caregivers although their children don’t have diarrhoea.
Keywords: Caregivers; Dehydration; Oral rehydration solution; Practices